Shipping in an era of digital transformation - Jörn Quitzau; Niklas Tontara; Henning Vöpel; Malte Jahn; Alkis Henri Otto; André Wolf (Berenberg Bank und Hamburgisches WeltWirtschaftsInstitut (HWWI), 2018)
[Introduction] The world is currently experiencing an economic boom. All of the major economic areas - the USA, Europe, Japan and China - are seeing strong economic growth. But beyond current favourable conditions there are signs that the world is currently undergoing a fundamental transition and that it will continue to change significantly in the coming years. Consequently, the macroeconomic environment is subject to a great deal of uncertainty in the medium and longer term. Is this the start of a new era of economic isolation? What effects will the changing demographic patterns have? What will be the extent of the impact of climate change and the resulting environ mental policy measures? What are the consequences of the digital transformation for the economy in general and for the trade of goods in particular? These questions affect large sections of our economy and our society. The shipping industry is impacted directly or at least indirectly by many of these questions surrounding the future. The unusually high level of uncertainty for the shipping sector poses a special challenge in this context, particularly as shipping has been undergoing a process of consolidation since the global financial and economic crisis and the existing excess capacities have not yet been reduced. This publication does not constitute a forecast on our part regarding the specific development of the shipping market. Instead, we aim to outline the economic framework upon which the industry must base its future decisions. We focus here on the process of digital transformation, and our analysis shows that the environment for shipping will remain very challenging in the years ahead.
Keywords: 330